FeCoP hollow nanocube composite material loaded on carbon cloth substrate and preparation method of FeCoP hollow nanocube composite material

By preparing FeCoP hollow nanocube composite materials on a carbon cloth substrate, the problems of low stability and catalytic activity of existing catalysts are solved, and an efficient electrocatalytic water decomposition reaction is achieved, cost is reduced, and excellent catalytic performance and stability are provided.

CN119710774AActive Publication Date: 2025-03-28CHINESE PEOPLES LIBERATION ARMY UNIT 61699
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411710738.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-03-28
Estimated Expiration
2044-11-27

AI Technical Summary

Technical Problem

The existing catalysts have low stability and catalytic activity during water cracking, and the precious metal catalysts are costly, making it difficult to achieve efficient and reusable water cracking applications.

Method used

FeCoP hollow nanocube composite material supported on a carbon cloth substrate was used to uniformly grow FeCoPrussian blue analog on the carbon cloth by co-precipitation method. Through continuous oxidation and local low-temperature solid-phase phosphating process, FeCoP@CC hollow nanocube composite catalyst with excellent catalytic performance was prepared.

Benefits of technology

It realizes efficient catalytic hydrogen evolution, oxygen evolution and full water dissolution reactions in the electrocatalytic water decomposition process, with excellent catalytic activity and stability, reducing reaction costs, and providing a low-cost and efficient new catalyst solution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119710774A_ABST
    Figure CN119710774A_ABST
Patent Text Reader

Abstract

The invention provides a FeCoP hollow nanocube composite material loaded on a carbon cloth substrate and a preparation method of the FeCoP hollow nanocube composite material, firstly, a FeCo Prussian blue analogue FeCo-PBAs is uniformly grown on conductive carbon cloth through a coprecipitation method, and then the FeCo Prussian blue analogue FeCo-PBAs is subjected to continuous oxidation and local low-temperature solid-phase phosphating process to obtain a FeCoP-CC hollow nanocube composite catalyst. The catalyst provided by the invention is a non-noble metal catalyst, can reduce the reaction cost, and has good catalytic activity on hydrogen evolution and oxygen evolution of electrolyzed water and electro-catalysis full water splitting. The FeCoP-CC hollow nanocube composite catalyst prepared by the invention can be used in an electrocatalytic water decomposition reaction, and effectively solves the technical problems of low catalytic efficiency, low reserves and high cost of an existing catalyst on electrochemical reaction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of preparation of multi-component bimetallic phosphide nanocomposite materials, and in particular relates to a FeCoP hollow nanocube composite material loaded on a carbon cloth substrate and a preparation method thereof. Background Art

[0002] In today's society, human development is closely related to energy. In the past two centuries, human energy supply has mainly relied on non-renewable fossil fuels such as oil and natural gas. However, with the increasing depletion of consumable energy such as oil and coal and the many environmental problems caused by the burning of mineral fuels, such as global warming, air and water pollution, it is urgent to find a new green and recyclable energy. Among many energy sources, hydrogen energy stands out. It has the advantages of high combustion calorific value, pollution-free combustion, abundant raw materials, convenient storage and transportation, and is a highly competitive clean energy. Among various hydrogen production methods, water electrolysis has become the most ideal hydrogen production method due to its abundant raw materials and the recyclability of hydrogen production and utilization. However, in the process of hydrogen and oxygen production, complex electron transfer and slow kinetic processes limit the large-scale application of water splitting. At present, commercial electrocatalysts are mainly based on precious metals such as platinum, iridium oxide or ruthenium oxide, and the high price also limits the application of water splitting. At the same time, powder material catalysts need to add organic binders during use, which may increase the internal resistance of the system, reduce the service life, and make it difficult to recycle. Therefore, finding efficient, reusable and cheap metal catalysts has become a necessary step to realize water splitting applications. Summary of the invention

[0003] 1. Technical issues to be resolved

[0004] The present invention provides a FeCoP hollow nanocube composite material supported on a carbon cloth substrate and a preparation method thereof, so as to solve the technical problems of low stability and catalytic activity of existing catalysts and high cost of precious metals and their oxides.

[0005] (II) Technical solution

[0006] In order to solve the above technical problems, the present invention proposes a method for preparing a FeCoP hollow nanocube composite material supported on a carbon cloth substrate, the preparation method comprising the following steps:

[0007] S1. ultrasonically washing and drying the carbon cloth to obtain a treated carbon cloth;

[0008] S2. Disperse Co(NO3)2·6H2O and sodium citrate in deionized water and stir them evenly with magnetic force, which is marked as solution A; disperse potassium ferrocyanide in deionized water, which is marked as solution B; under continuous magnetic stirring, drip solution B into solution A drop by drop to react and obtain a mixed solution, which is marked as solution C;

[0009] S3. Immerse the treated carbon cloth obtained in step S1 into the solution C obtained in step S2, let it stand at room temperature, take out the carbon cloth, wash it with deionized water and ethanol for multiple times, and dry it at a constant temperature in vacuum to obtain a carbon cloth loaded with FeCo-PBAs precursor;

[0010] S4. Place the carbon cloth loaded with FeCo-PBAs precursor obtained in step S3 into an Al2O3 porcelain boat, place the porcelain boat in a muffle furnace, heat it to 250-300°C, perform the first oxidation, then continue to heat it to 300-400°C, perform the second oxidation, and after the tubular furnace is naturally cooled to room temperature, obtain a carbon cloth loaded with FeCoOx nanocube composite material;

[0011] S5. Place the carbon cloth loaded with FeCoOx nanocube composite material obtained in step S4 into an Al2O3 porcelain boat, place the porcelain boat downstream of the tube furnace, place another porcelain boat filled with NaH2PO2·H2O upstream of the tube furnace, heat to 300-450°C, keep warm for 2-4h, and then cool naturally to room temperature to obtain a solid preform;

[0012] S6. The solid preform obtained in step S5 is dispersed in deionized water, stirred, centrifuged and washed to remove excess P powder;

[0013] S7. Repeat step S6 for multiple times, then wash with ethanol, centrifuge, and dry to obtain a FeCoP hollow nanocube composite material supported on a carbon cloth substrate.

[0014] Furthermore, in step S1, the carbon cloth is ultrasonically washed in acetone, ethanol and aqueous solution in sequence, then ultrasonically washed in concentrated HNO3 for 4 to 4.5 hours, and then washed with water.

[0015] Furthermore, in step S2, the concentration of Co(NO3)2·6H2O in solution A is 5-7 mmol, the concentration of sodium citrate is 8-10 mmol; the concentration of potassium ferrocyanide in solution B is 3-5 mmol; and the volume ratio of solution A to solution B is 1:1.

[0016] Furthermore, in step S3, the size of the carbon cloth is 1×2 cm 2 , let stand at room temperature for 12 to 36 hours, the drying temperature is 60 to 62°C, and the drying time is >10 hours.

[0017] Further, in step S4, the temperature is increased to 250-300°C at a heating rate of 0.5-2°C / min in an air atmosphere for the first oxidation, and maintained at this temperature for 1-2 hours, and then the temperature is further increased to 300-400°C at a heating rate of 2-10°C / min for the second oxidation, and maintained at this temperature for 0.5-1 hour.

[0018] Furthermore, in step S5, the mass of NaH2PO2·H2O is 1 to 2 g.

[0019] Furthermore, in step S5, the temperature is increased to 300-450° C. at a heating rate of 2-5° C. / min under an argon atmosphere.

[0020] Furthermore, in step S6, stirring is performed for 30 to 60 minutes.

[0021] Furthermore, in step S7, step 6 is repeated 4 to 5 times.

[0022] In addition, the present invention also provides a FeCoP hollow nanocube composite material supported on a carbon cloth substrate, and the composite material is prepared by the above method.

[0023] (III) Beneficial effects

[0024] The present invention proposes a FeCoP hollow nanocube composite material supported on a carbon cloth substrate and a preparation method thereof. First, FeCo Prussian blue analog FeCo-PBAs are uniformly grown on a conductive carbon cloth by a coprecipitation method, and then continuous oxidation and local low-temperature solid-phase phosphating processes are performed to obtain a FeCoP@CC hollow nanocube composite catalyst. The catalyst of the present invention is a non-precious metal catalyst, which can reduce the reaction cost and has good catalytic activity for hydrogen evolution, oxygen evolution and electrocatalytic water splitting by electrolysis of water. The FeCoP@CC hollow nanocube composite catalyst prepared by the present invention can be used in electrocatalytic water decomposition reactions, effectively solving the technical problems of low catalytic efficiency, low reserves and high cost of existing catalysts for electrochemical reactions.

[0025] The beneficial effects of the present invention specifically include:

[0026] 1. The present invention uses FeCo Prussian blue analogs (FeCo-PBAs) nanocubes as precursors and sacrificial templates, constructs them on carbon cloth by a co-precipitation method at room temperature, and obtains a hollow multi-component bimetallic phosphide nanocomposite catalyst with excellent catalytic performance through subsequent continuous oxidation and local low-temperature solid-phase phosphating processes.

[0027] 2. The FeCoP@CC hollow nanocube composite material obtained by the present invention can promote the transfer of electrons to a great extent by improving the conductivity of the material and exposing more active sites by compounding with a conductive substrate. The synergistic coupling between the matrix and the active material can also improve the activity and stability, thereby enhancing the electrocatalytic activity of the initial material. The synergistic effect between the two components can optimize the electronic structure of the material, adjust the adsorption energy of the intermediate, and thus optimize the performance of the material. Therefore, it exhibits excellent catalytic activity when used for hydrogen evolution reaction (HER), oxygen evolution reaction (OER) and overall water splitting reaction. At a current density of 10 mA / cm 2 When the overpotential is 74mV, 219mV and 1.58V respectively. After long-term stability test under constant voltage, the current remains almost constant, showing excellent catalytic stability.

[0028] 3. As a non-precious metal catalyst, this material is used for electrocatalytic water splitting and exhibits excellent electrocatalytic activity, which can reduce the reaction cost and provide a new idea for the preparation of low-cost, high-catalytic activity, and good stability new catalysts for renewable energy conversion.

[0029] 4. The present invention is used to prepare FeCoP@CC hollow nanocube composite materials, and the prepared materials can be used in electrocatalytic water splitting reactions. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 XRD spectra of Fe-Co PBAs, FeCoOx and FeCoP supported on carbon cloth prepared in Example;

[0031] Figure 2 XRD spectra of FeP and CoP nanocomposites prepared in Comparative Examples 1 and 2;

[0032] Figure 3 is a scanning electron microscope (SEM) image of the carbon cloth after treatment in Example;

[0033] Figure 4 Scanning electron microscope (SEM) images of FeCo-PBAs@CC nanocubes prepared in Example (a is a SEM image of FeCo-PBAs@CC at high magnification; b is a SEM image of FeCo-PBAs@CC at low magnification);

[0034] Figure 5 Transmission electron microscopy (TEM) image of FeCo-PBAs nanocubes prepared in Example;

[0035] Figure 6Scanning electron microscope (SEM) images of FeCoOx, FeCoP, FeP and CoP nanocomposites supported on carbon cloth prepared in Example, Comparative Examples 1 and 2 (a, b are SEM images of FeCoOx at high magnification and low magnification, respectively; c, d are SEM images of FeCoP at high magnification and low magnification, respectively; e, f are SEM images of FeP at high magnification and low magnification, respectively; g, h are SEM images of CoP at high magnification and low magnification, respectively);

[0036] Figure 7 Transmission electron microscope (TEM) images of FeCoOx nanocubes prepared in Example (a is a TEM image of FeCoOx at high magnification, and b is a TEM image of FeCoOx at low magnification);

[0037] Figure 8 HRTEM image of FeCoOx nanocubes prepared in Example (the inset is the selected area electron diffraction image of FeCoOx);

[0038] Fig. 9 Transmission electron microscopy (TEM) images of FeCoP nanocubes prepared in Example (a is a TEM image of FeCoP at high magnification, and b is a TEM image of FeCoP at low magnification);

[0039] Fig.10 HRTEM image of FeCoP nanocubes prepared in Example;

[0040] Fig.11 Element distribution diagram of the high-angle annular dark field image-scanning transmission electron image of the FeCoP nanocube prepared in the example (a is the HAADF-STEM photo of FeCoP; b is the element distribution diagram of Co; c is the element distribution diagram of Fe, and d is the element distribution diagram of P);

[0041] Fig.12 Linear sweep (LSV) curves of the hydrogen evolution reaction of FeCo-PBAs precursors, FeCoOx, CoP, FeP, FeCoP nanocomposites and commercial Pt / C prepared in examples and comparative examples 1 and 2 in alkaline electrolyte;

[0042] Fig.13 Tafel slope plots of hydrogen evolution reactions of FeCo-PBAs precursors, FeCoOx, CoP, FeP, FeCoP nanocomposites and commercial Pt / C prepared in examples, comparative examples 1 and 2 in alkaline electrolytes;

[0043] Fig.14The effective activity area diagram of the hydrogen evolution reaction of FeCo-PBAs precursors, FeCoOx, CoP, FeP, FeCoP nanocomposites and commercial Pt / C prepared in examples, comparative examples 1 and 2 in alkaline electrolyte;

[0044] Fig.15 AC impedance diagrams of hydrogen evolution reactions of FeCo-PBAs precursors, FeCoOx, CoP, FeP, FeCoP nanocomposites and commercial Pt / C prepared in examples and comparative examples 1 and 2 in alkaline electrolytes;

[0045] Fig.16 A multi-step current process diagram of the hydrogen evolution reaction of the FeCoP@CC nanocomposite prepared in the example in an alkaline electrolyte;

[0046] Fig.17 The curve diagram of the change of current over time of the hydrogen evolution reaction of water electrolysis under constant voltage for the FeCoP@CC nanocomposite prepared in Example;

[0047] Fig.18 Linear sweep (LSV) curves of the oxygen evolution reaction of FeCo-PBAs precursors, FeCoOx, CoP, FeP, FeCoP nanocomposites and commercial IrO2 prepared in examples and comparative examples 1 and 2 in alkaline electrolyte;

[0048] Fig.19 Tafel plots of oxygen evolution reactions of FeCo-PBAs precursors, FeCoOx, CoP, FeP, FeCoP nanocomposites and commercial IrO2 prepared in examples, comparative examples 1 and 2 in alkaline electrolytes;

[0049] Fig. 20 AC impedance diagrams of hydrogen evolution reactions of FeCo-PBAs precursors, FeCoOx, CoP, FeP, FeCoP nanocomposites and commercial IrO2 prepared in examples and comparative examples 1 and 2 in alkaline electrolytes;

[0050] Fig.21 The figure is a comparison diagram of polarization curves of the FeCoP@CC nanocomposite prepared in Example before and after 1000 cycles of electrocatalytic water decomposition and oxygen evolution reaction in alkaline electrolyte, where "■" represents 1 cycle and "●" represents 1000 cycles; the inset is a curve of the change of current over time of the FeCoP@CC nanocomposite prepared in Example 2 under constant voltage for electrocatalytic water decomposition and oxygen evolution reaction;

[0051] Fig. 22The SEM image of the FeCoP@CC nanocomposite prepared in the example after 1000 cycles of oxygen evolution reaction (a is the SEM image of FeCoP@CC at a high magnification, and b is the SEM image of FeCoP@CC at a low magnification);

[0052] Fig.23 Linear sweep (LSV) curves of FeCoP, CoP, FeP and IrO2 / CC / / Pt / C / CC nanocomposites coated with nitrogen-doped carbon nanocages prepared in the examples for electrocatalytic overall water splitting in alkaline electrolyte;

[0053] Fig.24 This is a curve of the change in current over time of the FeCoP@CC nanocomposite material prepared in the example under constant voltage for electrocatalytic complete water splitting reaction. DETAILED DESCRIPTION

[0054] In order to make the purpose, content and advantages of the present invention more clear, the specific implementation methods of the present invention are further described in detail below in conjunction with the drawings and examples.

[0055] Example

[0056] This embodiment provides a method for preparing a FeCoP hollow nanocube composite material supported on a carbon cloth substrate, the preparation method comprising the following steps:

[0057] S1. The carbon cloth (CC) was ultrasonically washed in acetone, ethanol and aqueous solution in sequence for 30 min each, then ultrasonically washed in concentrated HNO3 for 4 h, then washed with water for 30 min, and dried at 60 ° C to obtain the treated carbon cloth;

[0058] S2. Disperse 1.75 g Co(NO3)2·6H2O and 2.65 g sodium citrate into 200 mL deionized water and stir evenly with magnetic force, which is labeled as solution A. Disperse 1.32 g potassium ferrocyanide (K3[Fe(CN)6]) into 200 mL deionized water, which is labeled as solution B. Under continuous magnetic stirring, add solution B dropwise into solution A and react for 2 min to obtain a mixed solution, which is labeled as solution C.

[0059] S3. Immerse the treated carbon cloth obtained in step S1 into the solution C obtained in step S2. The size of the carbon cloth is 1×2 cm 2 , standing at room temperature for 24 hours, taking out the carbon cloth, washing it with deionized water and ethanol for multiple times, and drying it at a constant temperature in vacuum at a drying temperature of 60°C for a drying time of more than 10 hours, to obtain a carbon cloth loaded with a bimetallic FeCo Prussian blue analog FeCo-PBAs precursor;

[0060] S4. Place the carbon cloth loaded with FeCo-PBAs precursor obtained in step S3 into an Al2O3 porcelain boat, place the porcelain boat in a muffle furnace, heat it to 270°C at a heating rate of 0.5°C / min in an air atmosphere, perform the first oxidation, and keep it at this temperature for 1 hour, then continue to heat it to 350°C at a heating rate of 5°C / min, perform the second oxidation, and keep it at this temperature for 0.5 hour, and after the tubular furnace is naturally cooled to room temperature, obtain the carbon cloth loaded with FeCoOx nanocube composite material;

[0061] S5. Place the carbon cloth loaded with FeCoOx nanocube composite material obtained in step S4 into an Al2O3 porcelain boat, place the porcelain boat in the downstream of the tube furnace, place another porcelain boat loaded with 2g of NaH2PO2·H2O in the upstream of the tube furnace, heat the mixture to 300°C at a heating rate of 2°C / min under an argon atmosphere, keep the mixture in an Ar atmosphere for 2h, and then cool the mixture naturally to room temperature to obtain a solid preform;

[0062] S6. The solid preform obtained in step S5 is dispersed in deionized water, stirred for 30 to 60 minutes, and centrifuged to remove excess P powder;

[0063] S7. Repeat step S6 4 ​​to 5 times, then wash with ethanol, centrifuge, and dry to obtain a FeCoP hollow nanocube composite material supported on a carbon cloth substrate (FeCoP@CC nanocomposite material).

[0064] Comparative Example 1

[0065] This comparative example proposes a method for preparing a FeP nanocube composite material supported on a carbon cloth substrate, the preparation method comprising the following steps:

[0066] S1. The carbon cloth was ultrasonically washed in acetone, ethanol and aqueous solution in sequence for 30 min each, then ultrasonically washed in concentrated HNO3 for 4 h, then washed with water for 30 min, and dried at 60 ° C to obtain the treated carbon cloth;

[0067] S2. Dissolve 3.8 g polyvinyl pyrrolidone PVP and 0.11 g K4[Fe(CN)6] in 50 mL 0.1 M hydrochloric acid solution and stir for 30 min until the solution becomes clear.

[0068] S3. Immerse the treated carbon cloth obtained in step S1 into the solution obtained in step S2. The size of the carbon cloth is 1×2 cm 2 , the solution was heated to 80°C in an oven and maintained for 24 hours. After the reaction was completed, the carbon cloth was taken out, washed with deionized water and ethanol for several times, and then dried at a constant temperature of 60°C in a vacuum oven for more than 10 hours to obtain a carbon cloth loaded with a Prussian blue PB precursor;

[0069] S4. Place the carbon cloth loaded with the PB precursor obtained in step S3 into an Al2O3 porcelain boat, then place the porcelain boat in a muffle furnace, heat it to 270°C at a heating rate of 0.5°C / min in an air atmosphere, perform the first oxidation, and keep it at this temperature for 1 hour, then continue to heat it to 350°C at a heating rate of 5°C / min, perform the second oxidation, and keep it at this temperature for 0.5h, and after the tubular furnace is naturally cooled to room temperature, obtain a carbon cloth loaded with Fe2O3 nanocube composite material;

[0070] S5. Place the carbon cloth loaded with Fe2O3 nanocube composite material obtained in step S4 into an Al2O3 porcelain boat, place the porcelain boat in the downstream of the tube furnace, place another porcelain boat loaded with 2g of NaH2PO2·H2O in the upstream of the tube furnace, heat the mixture to 300°C at a heating rate of 2°C / min under an argon atmosphere, keep the mixture in an Ar atmosphere for 2h, and then cool the mixture naturally to room temperature to obtain a solid preform;

[0071] S6. The solid preform obtained in step S5 is dispersed in deionized water, stirred for 30 to 60 minutes, and centrifuged to remove excess P powder;

[0072] S7. Repeat step S6 4 ​​to 5 times, then wash with ethanol, centrifuge, and dry to obtain a FeP nanocube composite material supported on a carbon cloth substrate (FeP@CC nanocomposite material).

[0073] Comparative Example 2

[0074] This comparative example proposes a method for preparing a CoP nanocube composite material supported on a carbon cloth substrate, the preparation method comprising the following steps:

[0075] S1. The carbon cloth was ultrasonically washed in acetone, ethanol and aqueous solution in sequence for 30 min each, then ultrasonically washed in concentrated HNO3 for 4 h, then washed with water for 30 min, and dried at 60 ° C to obtain the treated carbon cloth;

[0076] S2. Disperse 1.75g ​​Co(NO3)2·6H2O and 2.65g sodium citrate into 200mL deionized water and stir evenly with magnetic force, which is marked as solution A; disperse 1.32g K3Co(CN)6 into 200mL deionized water, which is marked as solution B; under continuous magnetic stirring, drip solution B into solution A drop by drop, react for 2min, and obtain a mixed solution, which is marked as solution C;

[0077] S3. Immerse the treated carbon cloth obtained in step S1 into the solution C obtained in step S2. The size of the carbon cloth is 1×2 cm 2, let it stand at room temperature for 24 hours, then take out the carbon cloth, wash it with deionized water and ethanol for several times, and then dry it at a constant temperature in vacuum at a drying temperature of 60°C for a drying time of more than 10 hours to obtain a carbon cloth loaded with a bimetallic CoCo Prussian blue analog CoCo-PBAs precursor;

[0078] S4. Place the carbon cloth loaded with the CoCo-PBAs precursor obtained in step S3 into an Al2O3 porcelain boat, then place the porcelain boat in a muffle furnace, heat it to 270°C at a heating rate of 0.5°C / min in an air atmosphere, perform the first oxidation, and keep it at this temperature for 1 hour, then continue to heat it to 350°C at a heating rate of 5°C / min, perform the second oxidation, and keep it at this temperature for 0.5h, and after the tubular furnace is naturally cooled to room temperature, a carbon cloth loaded with Co3O4 nanocube composite material is obtained;

[0079] S5. Place the carbon cloth loaded with Co3O4 nanocube composite material obtained in step S4 into an Al2O3 porcelain boat, place the porcelain boat in the downstream of the tube furnace, place another porcelain boat loaded with 2g of NaH2PO2·H2O in the upstream of the tube furnace, heat the mixture to 300°C at a heating rate of 2°C / min under an argon atmosphere, keep the mixture warm for 2h under an Ar atmosphere, and then cool the mixture naturally to room temperature to obtain a solid preform;

[0080] S6. The solid preform obtained in step S5 is dispersed in deionized water, stirred for 30 to 60 minutes, and centrifuged to remove excess P powder;

[0081] S7. Repeat step S6 4 ​​to 5 times, then wash with ethanol, centrifuge, and dry to obtain a CoP hollow nanocube composite material supported on a carbon cloth substrate (CoP@CC nanocomposite material).

[0082] The XRD spectra of FeCo-PBAs, FeCoOx and FeCoP nanocubes prepared in the examples are shown in Figure 1As shown in the figure, it can be seen that, except for the peak of the carbon cloth substrate, the peak of Fe-Co PBAs coincides with the face-centered cubic structure of Co3[Fe(CN)6]2·10H2O, corresponding to PDF card 46-0907. In order to avoid the influence of CC on the test, the powders of FeCoOx and FeCoP were scraped off from CC during the test. It can be seen from the figure that the FeCoOx nanocubes show diffraction peaks at 31.2°, 36.845° and 65.2°, which can be attributed to the (220), (311) and (440) crystal planes of Co3O4 (JCPDS No.43-1003), while the diffraction peaks at 30.3°, 35.6° and 63.0° are consistent with the (206), (119) and (4012) crystal planes of Fe2O3 (JCPDS No.25-1402), respectively, indicating that the Fe-Co PBAs precursor has been successfully converted into FeCoOx nanocomposites through the continuous oxidation process. At the same time, the diffraction peaks of the FeCoP nanocomposite can be well matched with the PDF standard cards of Co2P (JCPDS No.32-0306), CoP (JCPDS No.29-0497) and FeP4 (JCPDS No.34-0995), indicating that the FeCoOx nanocomposite is phosphated into FeCoP after continuous oxidation and then low-temperature phosphating.

[0083] The XRD spectra of FeP and CoP nanocubes prepared in Comparative Examples 1 and 2 are as follows: Figure 2 As shown in the figure, it can be seen that FeP and CoP nanocubes were synthesized through similar continuous oxidation and low-temperature solid-phase phosphating processes.

[0084] Scanning electron microscope (SEM) image of blank carbon cloth Figure 3 shown.

[0085] The scanning electron microscope (SEM) image of the FeCo-PBAs nanocubes prepared in the example is as follows: Figure 4 As shown, the transmission electron microscope (TEM) image of the FeCo-PBAs nanocubes prepared in the embodiment is as follows Figure 5 As shown. Compared with blank carbon cloth ( Fig. 9 ), after co-precipitation, a layer of nanocubes with regular shape and uniform size grew on the surface of the carbon cloth, and the particle size of the cubes was about 200nm and the surface was smooth.

[0086] The scanning electron microscope (SEM) images of FeCoOx and FeCoP prepared in Example 1, FeP prepared in Comparative Example 1, and CoP nanocubes prepared in Comparative Example 2 are as follows: Figure 6As shown in the figure, it can be seen that after the late continuous oxidation and subsequent low-temperature phosphating process of Fe-Co PBAs@CC, PB@CC and Co-CoPBAs@CC nanocubes, the formed nanocomposites can still grow well on CC and inherit the nanocube morphology of Fe-Co PBAs, PB and Co-Co PBAs precursors, but the surface of the formed CoP nanocomposite is smoother.

[0087] The transmission electron microscope (TEM) image of the FeCoOx nanocubes prepared in the example is as follows: Figure 7 As shown, the HRTEM image of the FeCoOx nanocubes prepared in the embodiment is as follows Figure 8 As shown, from Figure 7 and 8 It can be seen that FeCoOx synthesized by continuous oxidation of Fe-CoPBAs precursor can well maintain the nanocubic morphology of the precursor. The interior of FeCoOx is densely filled with many Co3O4 and Fe2O3 nanoparticles with a diameter of 5-20nm.

[0088] The transmission electron microscope (TEM) image of the FeCoP nanocubes prepared in the example is as follows: Fig. 9 As shown, the scanning electron microscope (HRTEM) image of the FeCoP nanocubes prepared in the embodiment is as follows Fig.10 As shown, the high-angle annular dark field image of the FeCoP nanocube prepared in the embodiment - the scanning transmission electron image of the scanning transmission microscope is as shown in FIG. Fig.11 As shown, from Figures 9-11 It can be seen that the FeCoP formed after low-temperature phosphating maintains the nanocube structure of FeCoOx well, but the entire nanocube becomes a hollow structure. It proves that the FeCoP nanocomposite has been successfully synthesized. In addition, high-latitude annular dark field scanning (HAADF-STEM) and the corresponding element distribution map also show that the five elements Co, Fe, P, N and C are evenly distributed on the carbon skeleton on the surface of FeCoP, which also shows that this method has successfully prepared FeCoP nanocubes.

[0089] The linear sweep (LSV) curves of the hydrogen evolution reaction of water electrolysis in alkaline electrolyte for FeCoOx and FeCoP prepared in Example 1, FeP prepared in Comparative Example 1, CoP nanocubes prepared in Comparative Example 2, and commercial Pt / C are shown in FIG. Fig.12 The Tafel slope diagram is shown in Fig.13 As shown in the figure, the effective active area diagram is as follows Fig.14 As shown, the AC impedance diagram is as follows Fig.15 As shown by Fig.12It can be seen that the performance of the FeCo-PBAs precursor is very poor, and the FeCoP@CC nanocomposite catalyst exhibits the best HER catalytic activity at a current density of 10 mA cm -2 (η 10 ), the overpotential relative to RHE is only 74 mV, which is lower than that of FeCoOx@CC, FeP@CC and CoP@CC nanocomposites (η 10 =-196, -185 and -160 mV vs. RHE). In addition, the slope of the catalyst is 74 mV / dec, which is also smaller than that of the other samples, indicating that FeCoP@CC has a good thermal conductivity at a current density of 10 mA / cm 2 When the current density increases with the overvoltage, it increases most rapidly, indicating that FeCoP@CC has a faster kinetic process in the process of catalytic water electrolysis and hydrogen production than other catalysts. Fig.14 It can be seen that the electrochemical effective active area of ​​FeCoP@CC is 12.9 mF / cm 2 , which is much larger than that of FeP@CC and CoP@CC, indicating that FeCoP@CC has more active sites at the solid-liquid interface, which is mainly due to the multi-shell structure of the catalyst. Fig.15 It can be seen that among all the catalysts, FeCoP@CC has the smallest charge transfer resistance, so the driving voltage required for charge migration of this material is small, that is, the FeCoP@CC nanoarray consumes the smallest voltage, which is also one of the reasons why the FeCoP@CC nanocomposite material has the best HER performance.

[0090] The multi-step current process of preparing FeCoP@CC nanocomposites is as follows Fig.16 As shown, Fig.17 Polarization curves of the FeCoP@CC nanoarray prepared in the example before and after 1000 cycles of electrocatalytic water decomposition and hydrogen evolution reaction in alkaline electrolyte, where "■" represents 1 cycle and "●" represents 1000 cycles. The inset is a curve of current change over time under constant voltage. It can be seen from the figure that the current density of the material decreases very little after long-term testing, indicating that the catalyst has excellent hydrogen evolution stability.

[0091] The linear sweep (LSV) curves of the oxygen evolution reaction of water electrolysis in alkaline electrolyte for Fe-Co PBAs@CC, FeCoOx@CC, FeCoP@CC nanocubes prepared in Example 1, FeP@CC nanocubes prepared in Comparative Example 2, CoP nanocubes CoP@CC prepared in Comparative Example 2, and commercial IrO2 / C are shown in Figure 2. Fig.18 The Tafel slope diagram is shown in Fig.19 As shown, the AC impedance diagram is as follows Fig. 20As shown in Figure 2, similar to the hydrogen evolution performance, the formed multi-component nanocomposite catalyst still has the best OER catalytic performance at a current density of 10 mA / cm 2 When the overpotential is only 219mV, it has both the smallest Tafel slope and the smallest charge transfer resistance.

[0092] Fig.21 This is a polarization curve diagram of the FeCoP nanomaterial prepared in the example before and after 1000 cycles of electrocatalytic water decomposition and oxygen evolution reaction in alkaline electrolyte, where "■" represents 1 cycle and "●" represents 1000 cycles. It can be seen from the figure that the current density of the material decreases very little after long-term testing, indicating that the catalyst has excellent OER stability.

[0093] SEM images of FeCoP@CC nanocube samples after 1000 cycles of CV Fig. 22 As shown in the figure, it can be seen that the surface of the catalyst has a slight change after a long period of testing, which indicates that the composition of the catalyst has changed during the OER process, and the phosphide has been converted into other substances, exposing the internal nanoparticles for electrochemical etching.

[0094] Based on the strong synergistic effect, the synthesized catalyst exhibits high activity and stability in catalyzing alkaline HER and OER. In view of this, it was assembled into a primary cell for electrocatalytic overall water splitting test. The linear sweep (LSV) curves of the FeCoP@CC nanocubes prepared in Example 1, the FeP@CC prepared in Comparative Example 1, and the CoP@CC prepared in Comparative Example 2 in the electrocatalytic overall water splitting reaction in alkaline electrolyte are shown as follows: Fig.23 As shown in the figure, the curve of current changing with time under constant voltage is as follows Fig.24 As shown in the figure, it can be seen that compared with single-component FeP@CC and CoP@CC, the battery composed of multi-component FeCoP@CC nanocomposite catalyst can drive the complete decomposition of water at 1.58V, and also has good stability, with almost no attenuation after 52h.

[0095] According to the above characterization results and electrochemical tests, it can be concluded that the FeCoP@CC nanocomposite material with high electrocatalytic activity and low cost is successfully prepared by this embodiment. The catalyst has excellent catalytic performance in the application of electrocatalytic water splitting experiment.

[0096] The FeCoP@CC hollow nanocube composite material obtained by the present invention can greatly promote the transfer of electrons by improving the conductivity of the material and exposing more active sites through composite with a conductive substrate. The synergistic coupling between the matrix and the active material can also improve the activity and stability, thereby enhancing the electrocatalytic activity of the initial material. The synergistic effect between the two components can optimize the electronic structure of the material, adjust the adsorption energy of the intermediate, and thus optimize the performance of the material. Therefore, it exhibits excellent catalytic activity when used for hydrogen evolution reaction (HER), oxygen evolution reaction (OER) and overall water splitting reaction. At a current density of 10 mA / cm 2 When the overpotential is 74mV, 219mV and 1.58V respectively. After long-term stability test under constant voltage, the current remains almost constant, showing excellent catalytic stability.

[0097] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a FeCoP hollow nanocube composite material supported on a carbon cloth substrate, characterized in that: The preparation method comprises the following steps: S1. ultrasonically washing and drying the carbon cloth to obtain a treated carbon cloth; S2. Disperse Co(NO3)2·6H2O and sodium citrate in deionized water and stir them evenly with magnetic force, which is marked as solution A; disperse potassium ferrocyanide in deionized water, which is marked as solution B; under continuous magnetic stirring, drip solution B into solution A drop by drop to react and obtain a mixed solution, which is marked as solution C; S3. Immerse the treated carbon cloth obtained in step S1 into the solution C obtained in step S2, let it stand at room temperature, take out the carbon cloth, wash it with deionized water and ethanol for multiple times, and dry it at a constant temperature in vacuum to obtain a carbon cloth loaded with FeCo-PBAs precursor; S4. Place the carbon cloth loaded with FeCo-PBAs precursor obtained in step S3 into an Al2O3 porcelain boat, place the porcelain boat in a muffle furnace, heat it to 250-300°C, perform the first oxidation, then continue to heat it to 300-400°C, perform the second oxidation, and after the tubular furnace is naturally cooled to room temperature, obtain a carbon cloth loaded with FeCoOx nanocube composite material; S5. Place the carbon cloth loaded with FeCoOx nanocube composite material obtained in step S4 into an Al2O3 porcelain boat, place the porcelain boat downstream of the tube furnace, place another porcelain boat filled with NaH2PO2·H2O upstream of the tube furnace, heat to 300-450°C, keep warm for 2-4h, and then cool naturally to room temperature to obtain a solid preform; S6. The solid preform obtained in step S5 is dispersed in deionized water, stirred, centrifuged and washed to remove excess P powder; S7. Repeat step S6 for multiple times, then wash with ethanol, centrifuge, and dry to obtain a FeCoP hollow nanocube composite material supported on a carbon cloth substrate.

2. The method for preparing a FeCoP hollow nanocube composite material supported on a carbon cloth substrate according to claim 1, characterized in that: In step S1, the carbon cloth is ultrasonically washed in acetone, ethanol and aqueous solution in sequence, then ultrasonically washed in concentrated HNO3 for 4 to 4.5 hours, and then washed with water.

3. The method for preparing a FeCoP hollow nanocube composite material supported on a carbon cloth substrate according to claim 1, characterized in that: In step S2, the concentration of Co(NO3)2·6H2O in solution A is 5-7 mmol, and the concentration of sodium citrate is 8-10 mmol; the concentration of potassium ferrocyanide in solution B is 3-5 mmol; and the volume ratio of solution A to solution B is 1:

1.

4. The method for preparing a FeCoP hollow nanocube composite material supported on a carbon cloth substrate according to claim 1, characterized in that: In step S3, the size of the carbon cloth is 1×2 cm 2 , let stand at room temperature for 12 to 36 hours, the drying temperature is 60 to 62°C, and the drying time is >10 hours.

5. The method for preparing a FeCoP hollow nanocube composite material supported on a carbon cloth substrate according to claim 1, characterized in that: In step S4, the temperature is raised to 250-300°C at a heating rate of 0.5-2°C / min in an air atmosphere for the first oxidation, and maintained at this temperature for 1-2 hours, and then the temperature is further raised to 300-400°C at a heating rate of 2-10°C / min for the second oxidation, and maintained at this temperature for 0.5-1 hour.

6. The method for preparing a FeCoP hollow nanocube composite material supported on a carbon cloth substrate according to claim 1, characterized in that: In step S5, the mass of NaH2PO2·H2O is 1 to 2 g.

7. The method for preparing a FeCoP hollow nanocube composite material supported on a carbon cloth substrate according to claim 1, characterized in that: In step S5, the temperature is increased to 300-450°C at a heating rate of 2-5°C / min in an argon atmosphere.

8. The method for preparing a FeCoP hollow nanocube composite material supported on a carbon cloth substrate according to claim 1, characterized in that: In step S6, stirring is performed for 30 to 60 minutes.

9. The method for preparing a FeCoP hollow nanocube composite material supported on a carbon cloth substrate according to claim 1, characterized in that: In step S7, step 6 is repeated 4 to 5 times.

10. A FeCoP hollow nanocube composite material supported on a carbon cloth substrate, characterized in that: The composite material is prepared by the method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Preparation method for cobalt-nickel bimetal metaphosphate nanometer array loaded on carbon cloth substrate

    CN110124704A

  • Fe-doped mos2 nano-material, preparation method therefor and use thereof

    US20210062350A1